2008
DOI: 10.1016/j.bone.2008.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the functional activity of the [A-4] amelogenin gene splice product in newborn mouse ameloblasts

Abstract: In the mouse tooth organ, shortly after birth, ameloblasts acquire their secretory phenotype, which is characterized by the prominent expression and subsequent secretion of two isoforms of amelogenin, M180 and M59 (LRAP, [A−4]). Amelogenin deposition into the ameloblast extracellular matrix promotes enamel biomineralization. A complex set of intercellular signaling events, reciprocal communications between the developing oral epithelium and its underlying dental mesenchyme, guide the expression of amelogenin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…This PCR analysis showed that the larger amelogenin splice variant containing all exons with the exception of exon 4, was specifically upregulated in TgLRAP pre-secretory ameloblasts. These PCR results showing an upregulation of full length (M180) amelogenin in response to increased LRAP are consistent with reports by Iacob and Veis, who found that when exogenous LRAP protein was added to the LS8 ameloblast lineage cell line M180 mRNA was upreguated 13.6 fold upregulation after 24hrs (Iacob and Veis, 2008). Xu and co-workers reported that amelogenin full length protein, but not LRAP can stabilize amelogenin mRNA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This PCR analysis showed that the larger amelogenin splice variant containing all exons with the exception of exon 4, was specifically upregulated in TgLRAP pre-secretory ameloblasts. These PCR results showing an upregulation of full length (M180) amelogenin in response to increased LRAP are consistent with reports by Iacob and Veis, who found that when exogenous LRAP protein was added to the LS8 ameloblast lineage cell line M180 mRNA was upreguated 13.6 fold upregulation after 24hrs (Iacob and Veis, 2008). Xu and co-workers reported that amelogenin full length protein, but not LRAP can stabilize amelogenin mRNA.…”
Section: Discussionsupporting
confidence: 91%
“…Addition of exogenous LRAP to mouse enamel organ derived LS8 cells showed co-localization with LRAP (referred to as A-4) and lysosomal-associated membrane protein 1 (LAMP1), as well as an activation of the nitric oxide signaling pathway (Iacob and Veis, 2008; Le et al, 2007)…”
Section: Introductionmentioning
confidence: 99%
“…A number of alternatively spliced amelogenin isoforms are found in the enamel matrix, but the importance, function and abundance of each isoform is incompletely understood [4, 7]. In the past decade, a mixture of enamel matrix proteins called Emdogain was identified and used with success in clinical dentistry to promote repair of hard and soft periodontal tissue [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that csLRAP might have similar effects on chondrogenic cell proliferation involving LAMP-1 protein but may have a different effect on mineralized tissue-forming cells like osteoblasts or cementoblasts. It has been suggested that LAMP-1 involves the enamel epithelial cell differentiation 20) and amelogenin gene expression in ameloblast cell line promoted by LRAP 38) . And recent studies have indicated that LAMP-1 expression could be involved in osteoblast MC3T3 differentiation and the regulation of calcification 39) .…”
Section: Discussionmentioning
confidence: 99%